Analisis Postur Kerja dengan RULA Guna Penilaian Tingkat Risiko Upper Extremity Work-Related Musculoskeletal Disorders. Studi Kasus PT. Mandiri Jogja Internasional - Titin Isna Oesman; Era Irawan; Petrus Wisnubroto (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2019)
Leather handycraft industry produces handicrafts such as bags, shoes, wallets, belts. On production process atcutting division, work posture condition is too bent. A preliminary study on 20 workers found musculoskeletal complaints was greater than 50% at 16 items, mostly in upper limbs. Based on these complaints, research was on work posture using RULA and Sympton Questionnaire. Research purposes was to determine the risk level and relationship with UEWMSDs on the worker. The result of RULA found that work posture with RULA score was 7 (seven) that means 3 (three) risk level that very high category, and needs to be repaired as soon as possible. Symptom Questionnaire answer related to worker's complaint, which are complaints of shoulder and arm pain was 50%, pain after work 1-4 years was 85%, duration of illness <1 hour was 85%, move to another part due to illness was 55%, pain increase when the activity was 100%, and pain reduce at rest was 90%. Base on the condition, it was needed to redesigned cutting table evaluated by RULA category 3 (three) based on anthropometry of workers